ANALYSIS OF CHEMICAL COMPOUNDS DISTINGUISHER FOR AGARWOOD QUALITIES - Gunawan Trisandi Pasaribu; Totok K. Waluyo; Gustan Pari (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2016)
Gaharu (Agarwood) is described as a fragrant-smelling wood that is usually derived from the trunk of the genus Aquilaria and Gyrinops (both of the family Thymelaeaceae), which have been infected by a particular disease. Based on Indonesian National Standard, agarwood can be classified into various grades, i.e. gubal gaharu, kemedangan and serbuk gaharu. The grading system is based on the color, weight and odor. It seems that such a grading is too subjective for agarwood classification. Therefore, to minimize the subjectivity, more objective agarwood grading is required, which incorporates its chemical composition and resin content. This research was conducted focusing on the analysis of the particular grade of agarwood originating from West Sumatra. The different types of agarwood qualities are: kemedangan C, teri C, kacangan C and super AB. Initially, the obtained agarwood samples were grounded to powder, extracted on a Soxhlet extractor using various organic solvents (i.e. n-hexane, acetone, and methanol). The agarwood-acetone extracts were analyzed using GC-MS to determine its chemical composition. The results showed a positive, linier relationship in which the resin yield increased with the increase in agarwood quality grades. GC-MS analysis revealed that several sesquiterpene groups can be found in kemedangan C, teri C, kacangan C and super AB qualities. It is interesting that aromadendrene could be identified or found in all agarwood quality grades. Therefore, it is presumed that the aromadendrene compounds can act as an effective chemical distinguisher for agarwood, whereby the greater the aromadendrene content, the better is the agarwood grade.